Techniques and considerations for monitoring swimmers` passive drag - Scurati, R.; Gatta, G.; Michielon, G.; Cortesi, M. (Journal of Sports Sciences, 2019)
Drag is the resistant force that opposes a swimmer displacing through water and significantly affects swimming performance. Drag experienced during active swimming is called active drag (Da), and its direct determination is still controversial. By contrast, drag experienced while gliding in a stable streamlined body position is defined as passive drag (Dp), and its assessment is widely agreed upon. Dp reduction preserves the high velocity gained with the push-off from the starting block or wall after starting and turning or improves the gliding phase of the breaststroke cycle. Hence, this paper reviewed studies on swimming that measured Dp under different conditions of gliding. In the present research, accurate descriptions of the main methods used to directly or indirectly determine Dp are provided and the main advantages, limitations and critical features of each method are discussed. Since Dp differs in methods but not in reported values and is consistent regardless of the measuring method, the information provided in this paper might allow coaches and practitioners to identify the most suitable method for assessing and determining the drag of their swimmers.